2009
DOI: 10.1161/strokeaha.108.542308
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Causes of Early-Onset Dementia in Japan

Abstract: Background and Purpose-Few studies are available that have addressed the prevalence of early-onset dementia (EOD), including early-onset Alzheimer disease and other forms of dementia in Japan. Methods-A 2-step postal survey was sent to all of the 2475 institutions providing medical or care services for individuals with dementia in Japan's Ibaraki prefecture (population, 2 966 000) requesting information on EOD cases. Data were then reviewed and collated. Results-We identified 617 subjects with EOD. The estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
126
3
12

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(147 citation statements)
references
References 21 publications
6
126
3
12
Order By: Relevance
“…25 The accuracy of these estimates is debatable, given the international differences that have been reported. 19 Awareness of YOD may have changed in recent years, with improvements in neuroimaging technology and diagnostic procedures that may influence the identification of cases with dementia. [27][28][29] The Australian Institute of Health and Welfare (AIHW) report 7 used United Kingdom estimates 17,18 for the under-60 age-group but data from a more recent meta-analysis 25 for the other age-groups.…”
Section: Epidemiological Studies Concerning Prevalence Incidence Anmentioning
confidence: 99%
“…25 The accuracy of these estimates is debatable, given the international differences that have been reported. 19 Awareness of YOD may have changed in recent years, with improvements in neuroimaging technology and diagnostic procedures that may influence the identification of cases with dementia. [27][28][29] The Australian Institute of Health and Welfare (AIHW) report 7 used United Kingdom estimates 17,18 for the under-60 age-group but data from a more recent meta-analysis 25 for the other age-groups.…”
Section: Epidemiological Studies Concerning Prevalence Incidence Anmentioning
confidence: 99%
“…It was reported that VaD was the first cause of senile dementia in Asian countries (Roman 2002;Zhang et al 2005;Ikejima et al 2009). The molecular mechanism of VaD onset is still not clear, and therapeutics related to its molecular mechanism has also been developed continuously in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…In China, VaD is more common than AD in rural compared to urban areas [35]. Given the rapid pace of development in China, it is not surprising that the most recent Chinese prevalence study showed an AD prevalence of 3.5% compared to 1.1% for VaD in those aged more than 65 years [14]. These patterns are repeated across Asian countries as shown in Tables 1a-1c.…”
Section: Subtypes Of Dementiamentioning
confidence: 91%
“…Hence, the low prevalence of VaD in some studies could be attributed to limited use of neuroimaging. Identification of subtypes of dementia without neuroimaging in China reported that 29% of demented patients had VaD [14] compared to a higher VaD diagnosis rate of 47% among patients who underwent brain computed tomography (CT) in Japan [10].…”
Section: Subtypes Of Dementiamentioning
confidence: 99%